Addressing common forms of child maltreatment: evidence‐informed interventions and gaps in current knowledge. Issue 3 (16th October 2012) - Pecora, Peter J.; Sanders, David; Wilson, Dee; English, Diana; Puckett, Alan; Rudlang‐Perman, Kristen
Abstract This paper reviews interventions for preventing the occurrence and recurrence of major types of child maltreatment. We begin with an overview of the challenges of establishing evidence‐based interventions to prevent child abuse and neglect in many countries, and underscore the importance of this need with child maltreatment incidence rates in the USA, and how much each type and subtype contribute to child out‐of‐home placement. Next, we identify the well‐supported, supported and promising interventions for each child maltreatment type and subtype, according to their level of research evidence using an evidence‐based clearing house. The paper closes with a discussion of the implications for practice, evaluation, policy and agency management, including intervention knowledge gaps that showcase areas that need additional practice research.